An exploration of the personal experiences of digital forensics analysts who work with child sexual abuse material on a daily basis: “you cannot unsee the darker side of life” - Strickland, Clare; Kloess, Juliane A.; Larkin, Michael (Frontiers in Psychology, 2023)
Digital forensics analysts are a specialist group of police officers who are involved in investigating cases of online child sexual exploitation and abuse (CSEA), and identifying and classifying child sexual abuse material (CSAM) according to levels of severity respectively. The existing literature that has examined this phenomenon suggests that this group of police officers are at greater risk of psychological harm as a result of being exposed to CSAM, and that working with this type of material has the potential to significantly affect their mental health and wellbeing. The study presented here used Interpretative Phenomenological Analysis (IPA) to explore digital forensics analysts’ personal experiences of working in this role, and with CSAM, on a daily basis, as well as how they feel this has impacted on them, and how they manage this. Seven digital forensics analysts from a specialist unit in the UK took part in semi-structured, in-person interviews. Three themes were identified, namely: (i) Once you know you cannot unknow, (ii) Constant struggle to decompress, and (iii) The ups and downs of working as a digital forensics analyst. Participants talked about the difficulty of escaping the reality of the sheer prevalence of CSEA, and that working as a digital forensics analyst ultimately takes a toll on one’s mental health and wellbeing. As a result of undertaking this work on a daily basis, participants reported experiencing symptoms comparable to compassion fatigue, secondary traumatic stress, and burnout, and reflected about the long-term or irreversible psychological effect that working in this role may have. Findings are discussed in relation to theoretical and practical implications, as well as directions for future research.